The Effect of Artificial Intelligence Technology on Corporate Greenwashing Level: Evidence from Chinese Listed Enterprises - Yang, Xiaotong; Ren, Ziyan; Xie, Yini (Transactions on Economics, Business and Management Research, 2024)
This study employs a fixed effects model to examine the impact of AI technology on corporate behavior based on data from Chinese A-share listed companies from 2012 to 2022. Findings show that artificial intelligence application can significantly reduce corporate greenwashing behavior, which remains robust after addressing endogeneity issues and conducting a series of robustness tests. Heterogeneity analysis reveals that property rights, industry, and regional factors influence AI’s inhibition of greenwashing. This study highlights the crucial role of AI in corporate governance and emphasizes the importance of optimizing green finance regulation.